The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1993
DOI: 10.1161/01.str.24.1.122
|View full text |Cite
|
Sign up to set email alerts
|

Autosomal dominant leukoencephalopathy and subcortical ischemic stroke. A clinicopathological study.

Abstract: Background and Purpose: We recently described an autosomal dominant syndrome characterized mainly by recurrent strokes and neuroimaging evidence of leukoencephalopathy. We now report the pathological findings in one of the affected subjects.Case Description: A 40-year-old woman experienced her first grand mal seizure in 1971. From 1983 on she suffered recurrent strokes, seizures, and psychiatric disturbances with depressions, manic episodes, and dementia. In 1988, after her fourth stroke, she became tetraplegi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
152
0
8

Year Published

1995
1995
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(164 citation statements)
references
References 9 publications
4
152
0
8
Order By: Relevance
“…This syndrome is characterised by a predisposition for stroke caused by diffuse angiopathy: the vascular damage, prevalently affecting small cerebral arteries, is situated in the vascular smooth muscle cells (VSMC), which are the only site of expression of the Notch3 gene in human adults (Joutel et al, 2000). Besides progressive degeneration of the VSMC, the vessels walls of CADASIL patients also show accumulation of a material of unknown composition presenting at electron microscope observation as a granular osmiophilic material (GOM) (Baudrimont et al, 1993).…”
Section: The Effects Of Notch Signallingmentioning
confidence: 99%
“…This syndrome is characterised by a predisposition for stroke caused by diffuse angiopathy: the vascular damage, prevalently affecting small cerebral arteries, is situated in the vascular smooth muscle cells (VSMC), which are the only site of expression of the Notch3 gene in human adults (Joutel et al, 2000). Besides progressive degeneration of the VSMC, the vessels walls of CADASIL patients also show accumulation of a material of unknown composition presenting at electron microscope observation as a granular osmiophilic material (GOM) (Baudrimont et al, 1993).…”
Section: The Effects Of Notch Signallingmentioning
confidence: 99%
“…Neuroimaging abnormalities such as cerebral white matter lesions (WMLs), lacunes, and microbleeds in the CADASIL patients are related to this cerebral small‐vessel histopathology 1. While CADASIL is considered a primarily ischemic form of vascular dementia, spontaneous intracerebral hemorrhage (ICH) has recently been reported in association with CADASIL,2, 3, 4, 5, 6 suggesting that the structural fragility of arterial walls may lead to ICH attacks. However, there are limited data describing the effects that the underlying structural changes related to CADASIL have on the occurrence of ICH and subsequent outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the myelin density is reduced in ageing (Ge et al, 2002;Bartzokis et al, 2003) and in disorders affecting the white matter such as multiple sclerosis (Fazekas et al, 2002;Keegan and Noseworthy, 2002), CADASIL (Baudrimont et al, 1993;Okeda et al, 2002), Binswangers disease (Roman, 1985) and vascular dementia (Wallin and Blennow, 1991).…”
Section: Introductionmentioning
confidence: 99%